Monte Carlo simulations and self-consistent field theory applied to calculations of density profiles in A1BA2 triblock copolymer melts - Dzięcielski, M.; Wołoszczuk, S.; Banaszak, M. (Polimery, 2014)
Using two complementary numerical methods, the lattice Monte Carlo simulations with parallel tempering and self-consistent field theory, we investigate the distribution of A1, B, and A2 segments in the lamellar nanostructure of A1BA2 triblock copolymer melts. While the lattice Monte Carlo method is in principle exact, it is limited by a variety of factors, such as finite size effects, long relaxation times required to reach the thermal equilibrium and geometry of the underlying lattice. It is also limited to chains consisting of relatively few segments. The self-consistent field theory, on the other hand, is free of the above limitations, but it is a mean-field approach which does not take into account the thermal fluctuations. Therefore we confront the results obtained from the two above methods and draw conclusions concerning both the comparison of the two methods and the localization of the A1 segments in the B domain with increasing length of the A1 block. For Monte Carlo simulations we employ two types of chains, 2-32-30 and 1-16-15, and for the self-consistent field theory we use the corresponding values of the thermodynamic incompatibility parameter, c/v.